2017
DOI: 10.1186/s12909-017-0962-8
|View full text |Cite
|
Sign up to set email alerts
|

Developing mentorship in a resource-limited context: a qualitative research study of the experiences and perceptions of the makerere university student and faculty mentorship programme

Abstract: BackgroundThe aim of mentorship is to build the mentees capacity, enhance their skills and improve their ability to produce desired outcomes. However, the mentoring relationship is vulnerable to a number of challenges that may undermine its effectiveness and sustainability. We aimed to explore the experiences and perceptions of student and junior faculty mentees and senior faculty mentors at the Makerere University College of Health Sciences and identify the key factors defined by mentees and mentors as necess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 19 publications
2
67
1
Order By: Relevance
“…Traditional hierarchical mentoring with unidirectional mentor-mentee relationships have worked well in large research institutes and shown transformative mentorship for junior faculty in the short [ 36 ] and long-term [ 37 ]. However, these relationships in regional settings can be time-consuming and challenging when mentors are faced with demands of working multiple roles (clinical, research, teaching) and having overlapping roles as mentors and supervisors [ 38 ]. We were not able to identify published literature that describes a dual-mentor model (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional hierarchical mentoring with unidirectional mentor-mentee relationships have worked well in large research institutes and shown transformative mentorship for junior faculty in the short [ 36 ] and long-term [ 37 ]. However, these relationships in regional settings can be time-consuming and challenging when mentors are faced with demands of working multiple roles (clinical, research, teaching) and having overlapping roles as mentors and supervisors [ 38 ]. We were not able to identify published literature that describes a dual-mentor model (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Having time for mentoring in LMICs is often viewed as a luxury, and therefore, the development of mentoring capacities should be coupled by institutional commitment to the implementation of mentoring programs and recognition of the critical contribution of mentoring activities. In summary, the adoption of mentoring practices in LMICs is not a straightforward process of uptake and introduction but instead a complex implementation science issue requiring adaptation of existing approaches into different academic settings 13 (Table 1), until the needed structural change takes place.…”
Section: The Setting: Mentoring In Low- and Middle-income Countries (mentioning
confidence: 99%
“…Low- and middle-income countries and their regions share many commonalities but also present substantial cultural differences resulting from their individual characteristics and their specific past colonial influences. The oppressive histories in many countries have contributed to research and education structures with authoritarian approaches, 13,16 which in turn are additional obstacles for effective mentoring. Culture distills a deeply rooted respect for hierarchy and seniority (Table 1), which is echoed in medicine, academics, and research, 17 as well as strict formality in communication and dialog to the point that challenging the opinions of a senior scientist or faculty can often be considered offensive or inappropriate.…”
Section: Cross-cultural Perspectivesmentioning
confidence: 99%
“…Available studies mostly focus on institutional mentoring for medical or nursing students [14][15][16][17]. Several studies have examined mentors' and mentees' perceptions of their experiences, challenges and needs [18,19]. A recent study on the effectiveness of on-site mentoring in Indian maternity clinics examined the impact of mentoring on nurses' knowledge and clinics' readiness to provide services but did not consider the effectiveness of mentoring on provider practices [20].…”
Section: Introductionmentioning
confidence: 99%